Spectral Analysis of the Light Flash Produced by a Natural Dolomite Plate Under Strong Shock - 唐恩凌 徐名扬 张庆明 施晓涵 王猛 王迪 相升海 夏瑾 韩雅菲 张立佼 吴尽 张爽 袁健飞 (Plasma science & technology, 2015)
In order to obtain the elemental compositions of the projectile and target materials during 2A12 aluminum projectile shot on a natural dolomite plate, three kinds of experiments have been conducted using a spectral acquirement system established on a two-stage light gas gun for impact velocities ranging from 2.20 km/s to 4.20 km/s, at the same projectile incidence angle of 30°. Experimental results show that the elemental compositions of the projectile and target materials in the strong shock experiments have a good agreement with the original elemental compositions of the projectile and target. In addition, the relations between spectral radiant intensity and elemental compositions of the projectile and target materials have been obtained for different impact velocities, in which the spectral radiant intensity of the main elements in the material increases with increasing impact velocity, and more elements appear with increasing impact velocity since more energy would result from a higher velocity impact.